2015
DOI: 10.1186/s13012-015-0249-6
|View full text |Cite
|
Sign up to set email alerts
|

Early ART initiation among HIV-positive pregnant women in central Mozambique: a stepped wedge randomized controlled trial of an optimized Option B+ approach

Abstract: BackgroundDespite effective prevention strategies and increasing investments in global health, maternal to child transmission (MTCT) of HIV remains a significant problem globally, especially in sub-Saharan Africa. In 2012, there were 94,000 HIV-positive pregnant women in Mozambique. Approximately 15% of these women transmitted HIV to their newborn infants, resulting in nearly 14,000 new pediatric HIV infections that year. To address this issue, in 2013, the Mozambican Ministry of Health implemented the World H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Therefore, we concluded that sexual desire and fertility intentions are reversibly inhibited soon after the HIV diagnosis and reappear according to sociodemographic factors and initiation of ART in infected women. The positive impact of ART on fertility intentions in PLHIV has been reported in different studies 7, 14, 39…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, we concluded that sexual desire and fertility intentions are reversibly inhibited soon after the HIV diagnosis and reappear according to sociodemographic factors and initiation of ART in infected women. The positive impact of ART on fertility intentions in PLHIV has been reported in different studies 7, 14, 39…”
Section: Discussionmentioning
confidence: 70%
“…Pregnancy itself has been shown to be associated with poor retention in care in several countries [ 3 , 14 , 20 , 21 ]. One study in Malawi with early rollout of universal ART under Option B+ documented improved retention at 6 months postpartum (83%) although additional, larger retention studies in the era of Option B+ are ongoing [ 22 24 ]. The single factor associated with LFU in our multivariate analysis was never starting ART.…”
Section: Discussionmentioning
confidence: 99%
“…26 The intervention was implemented in 6 high-volume health centers providing PMTCT and ART services in the Mozambican National Health System. These health centers serve communities along the highly populated Beira highway and railway transport corridor that passes through Sofala and Manica provinces, from the port city of Beira on the Indian Ocean to the Zimbabwe border.…”
Section: Methodsmentioning
confidence: 99%